How useful is intraoperative cone beam computed tomography in maxillofacial surgery? An overview of the current literature. Issue 2 (February 2021) - Assouline, S.L.; Meyer, C.; Weber, E.; Chatelain, B.; Barrabe, A.; Sigaux, N.; Louvrier, A.
Abstract: Intraoperative imaging is increasingly used by surgeons and has become an integral part of many surgical procedures. This study was performed to provide an overview of the current literature on the intraoperative use of cone beam computed tomography (CBCT) imaging in maxillofacial surgery. A bibliographic search of PubMed was conducted in March 2020, without time limitation, using "intraoperative imaging" AND "maxillofacial surgery" AND "cone beam computed tomography" as key words. Ninety-one articles were found; after complete reading, 16 articles met the eligibility criteria and were analysed. The results showed that the majority of the indications were related to maxillofacial trauma, particularly zygomaticomaxillary complex fractures. Final verification with intraoperative CBCT before wound closure was the most common use of this device. However, innovative uses of intraoperative CBCT are expanding, such as CBCT coupling with mirror computational planning, and even the combined use of initial intraoperative CBCT acquisition with navigation. Immediate, fast, and easy evaluation of bone repositioning to avoid the need for further surgical revision is the main advantage of this technique. Imaging quality is comparable to that of multi-slice computed tomography, but with lower radiation exposure. Nevertheless, CBCT is still not widely available in maxillofacial centres, probably because of its cost, and perhaps because not everyone is aware of its advantages and versatility, which are reported in this review.